(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This paper discussed the impact on Banditry, Insurgents, Kidnapping and Terrorism on educational management in Nigeria. The paper is a review paper that depend secondary data. The secondary data were collected from print and online publications. The paper concluded that the impact of banditries, insurgencies, kidnapping and terrorism activities on educational management in Nigeria includes; unstable academic programme, death of professional teachers, destruction of infrastructure facilities and displacement of students and teachers. Based on this, the paper recommends that The Federal and state government of Nigeria should address the problem bleeding insecurities in Nigeria such like unemployment and porous board by providing opportunities and development programmes to engage the youth and deploy technology to provide securities in the board. Adequate funding should be provided for securities agencies for acquisition of modern weapons and for training.